Increased-rate stability studies for St John's wort (Hypericum perforatum), Ginkgo biloba and Kava Kava (Piper methysticum) under unfavourable environmental conditions - Eloff, Jacobus Nicolaas (University of Pretoria, 2013)
Dissertation (MSc (Pharmacology))--University of Pretoria, 2001.